Effects of glycyrrhetinic acid β on growth and virulence of Aeromonas hydrophila - Chen, Kai; Qin, Ting; Pan, Liangkun; Bing, Xuwen; Xi, Bingwen; Xie, Jun (Frontiers in Microbiology, 2023)
Aeromonas hydrophila is a significant pathogen to various aquaculture animals, and antibiotics are usually used to control bacterial diseases including fish diseases caused by A. hydrophila. Due to the severe situation of the development and spread of antibiotic resistance in pathogens, there are stricter restrictions on the antibiotics used in aquaculture. To evaluate the feasibility of using glycyrrhetinic acid β (GA) to replace antibiotics to control the A. hydrophila infection. In this study, the A. hydrophila isolated from diseased fish was used to test the antibacterial, anti-virulence activity in vitro and anti-infection effect in vivo of GA. Results in vitro showed that GA did not affect the growth of A. hydrophila, while it could down-regulate (P < 0.05) the mRNA expression of the hemolysis-related genes hly and aerA, and significantly inhibited (P < 0.05) the hemolytic activity of A. hydrophila. In addition, the results in vivo showed that oral administration of GA was ineffective in controlling acute infections caused by A. hydrophila. Taken together, these findings suggested that GA was a potential anti-virulence candidate against the A. hydrophila, and provided the basic data for the prevention and treatment of A. hydrophila-related diseases with GA.